2017
DOI: 10.18632/oncotarget.21211
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells-seeded bladder acellular matrix graft-silk fibroin enhances bladder reconstruction in a rat model

Abstract: The unfavourable clinical outcomes of host cell-seeded scaffolds for bladder augmentation warrant improved bioactive biomaterials. This study aimed to examine the feasibility of adipose-derived stem cells (ASCs)-seeded bilayer bladder acellular matrix graft (BAMG)-silk fibroin (SF) scaffold in enhancing bladder reconstruction. Sprague Dawley rats were randomly divided into three groups: the BAMG-SF-ASCs group, the acellular BAMG-SF group and the cystotomy group. The BAMG-SF-ASCs group was sampled at 2, 4 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Despite the functional and structural regeneration of the bioengineered neobladders described in several preclinical studies in rodents [ 87 , 136 ], limited and so far non efficient clinical translation has been reported. First, porous matrices composed of a diverse range of biomaterials alone or forming a composite of natural and synthetic nature were used for urinary bladder regeneration, with a wide range of outcomes in several clinical trials, and failed to meet their expectations in most cases (reviewed in [ 134 ]).…”
Section: Tissue Engineering For Urinary Bladder Regenerationmentioning
confidence: 99%
“…Despite the functional and structural regeneration of the bioengineered neobladders described in several preclinical studies in rodents [ 87 , 136 ], limited and so far non efficient clinical translation has been reported. First, porous matrices composed of a diverse range of biomaterials alone or forming a composite of natural and synthetic nature were used for urinary bladder regeneration, with a wide range of outcomes in several clinical trials, and failed to meet their expectations in most cases (reviewed in [ 134 ]).…”
Section: Tissue Engineering For Urinary Bladder Regenerationmentioning
confidence: 99%
“…ASCs are considered as the most suitable source of cells for stem cell-based therapies mainly because they can be harvested in large quantities using minimally invasive procedures 19 21 . It has been shown that ASCs secrete a wide variety of soluble mediators that promote morphological regeneration and functional restoration of bladder defects 22 24 . Possible triggering of cancer recurrence during remission remains, however, a significant concern in the application of stem cell-based therapies for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…To track SPIO-labeled NSCs in vivo, we chose early-passage NSCs (P2 or P3) and the SPIO labeling time of 12 hours. Early-passage NSCs were chosen over late-passage NSCs because they were exposed to the in vitro stress condition for a shorter period of time and hence might better represent cells in vivo 36, 37 . A 12-hour labeling time was also preferred to a 48- or 72-hour labeling time for the same reason, especially if it showed the same labeling efficiency as did the 48- or 72-hour labeling.…”
Section: Resultsmentioning
confidence: 99%